Vaccinium ashei reade: da análise fitoquímica das folhas ao desenvolvimento de nanopartículas e avaliação das atividades antioxidante e antidepressiva - Cezarotto, Verciane Schneider (2017)
The Vaccinium ashei Reade, known as blueberry, production and commercialization has become each time more popular due to its nutritional and pharmacological properties related to its consumption. Despite having a commercial interest focus on the fruits, studies have demonstrated that the leaves present high contents of phenolic compounds. This way, the current work was firstly evaluated the influence of the harvest period and cultivar on phenolic compounds profile, as well as the V. ashei leaves antioxidant activity. The second stage focused on the antidepressant activity evaluation of the hydroalcoholic extract from the V. ashei leaves belonging to the Climax cultivar (December/2013 collection) (HEV1). Through the evaluation of acute administration (10, 25 and 50 mg/Kg, p.o.), the animals immobility time was evaluated using forced swimming test (FST) and tail suspension test (TST). Besides, the effect of the chronic administration (50 mg/Kg, p.o.) was evaluated applying the unpredictable and moderate chronic stress test (UMCS). Lastly, it was developed nanostructures using Eudragit RS100 by the nanoprecipitation method with V. ashei leaves hydroalcoholic belonging to the Climax cultivar (March/2014 collection) (EHV2). The nanoparticles (NPEHV) were characterized and evaluated regarding the antioxidant effects. Furthermore, the antidepressant activity (1, 2.5, 5, 10 and 25 mg/Kg, p.o.) and the monoaminergic neurotransmitters involvement were in vivo evaluated. The results showed that the qualitative profile of the V. ashei leaves presented similarity in its composition; however, the proportion of each phenolic compound, as well as the antioxidant activity was influenced by the cultivar and collection period. Besides, the EHV1 acute administration (50 mg/Kg, p.o.) significantly reduced the immobility time of the animals during the FST and TST, without altering the locomotor acitivity in the open field test. The EHV1 chronic treatment (50 mg/Kg, p.o.) was also able to reverse the depressive-like behavior and the immobility time during the FST, without changing the body weight, haematological parameters and concentration of hepatic and cerebral glycogen of the animals submitted to the stress regimen. These results were not observed for the EHV2 acute administration (50 mg/Kg, p.o.). Nevertheless, the EHV2 nanoencapsulation was able to promote the antioxidant effects and antidepressant activity, involving dopaminergic and noradrenergic neurotrasmitters. The NPHEV presented physicochemical characteristics compatible with drug delivery nanosystems. In conclusion, the results indicate the therapeutic potential and a new formulation for V. ashei leaves, considered byproducts of fruits cultivation.